Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Tiga Raja Perkasa Jakarta - Aditya, Rama; Sosrowidigdo, Suryanto (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of workload and compensation on employee performance at PT Tiga Raja Perkasa. This study is motivated by the phenomenon of imbalance between job demands and reward systems that can affect employee productivity and work effectiveness. The research method used is a quantitative approach with a survey of all marketing employees. Data were collected through questionnaires and analyzed using multiple linear regression to test the relationship between variables. The results show that workload has a negative influence on employee performance, while compensation has a positive and significant effect. Simultaneously, both variables contribute to improving employee performance. These findings emphasize the importance of balance between workload and compensation systems in creating a productive and sustainable work environment